Is It Possible to Eliminate Postoperative Shunt Infections?: Results of a Modified Hydrocephalus Clinical Research Network Protocol - Elbaroody, Mohammad; Ezz, Adham; Eldessouky, Amr Helmy; Hassan, Ahmed A. Aziz N.; Elsharkawy, Ahmed Abbas; Ali, Khaled Bassim; Refaee, Ehab Ahmed El (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2023)
Background Postoperative shunt infection is a nightmare in neurosurgical practice with additional morbidity and mortality. A lot of protocols have contributed to the reduction of ventriculoperitoneal shunt (VPS) infections but not eradication. The aim of the study was to evaluate the rigid application of a modified Hydrocephalus Clinical Research Network (HCRN) protocol in the prevention of postoperative shunt infection.Methods We retrospectively evaluated children with congenital hydrocephalus who underwent VPS insertion, and in whom the protocol was applied from June 2019 to January 2020. Follow-up ranged from 11 to 24 months.Results Thirty-seven procedures were performed including 35 primary shunt insertions and two revision surgeries. The median age was 5 months (range, 1–30 months), and 25 patients were males. The most common cause for VPS placement was congenital hydrocephalus without identifiable cause in 28 cases (80%). The endoscope-assisted technique was used in the insertion of the proximal end in six cases (17%). The mean follow-up was 19.4 months (11–24 months). The rate of shunt infection was 0% till the last follow-up.Conclusion The preliminary results showed an effective method for the prevention of postoperative shunt infections using the modified protocol. These initial findings need to be validated in a large prospective study before widespread application can be recommended.
Keywords: ventriculoperitoneal; shunt infection; hydrocephalus complications